2005
DOI: 10.1021/ja0508931
|View full text |Cite
|
Sign up to set email alerts
|

A Nickel-Catalyzed Route to Pyridines

Abstract: A mild and general route for preparing pyridines from nitriles and diynes is described. Ni/imidazolyidene complexes were used to mediate cyclization alkynes and both aryl and alkyl nitriles at ambient temperature. In addition, the efficacy of this protocol allows for the preparation of a fused seven-membered pyridone and for intermolecular cyclizations. When an asymmetrical diyne was employed, cyclization afforded a single pyridine regioisomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 219 publications
(69 citation statements)
references
References 26 publications
2
67
0
Order By: Relevance
“…In this study, formation of a single regioisomer was observed. [52] The co-cyclotrimerization of two monoyne derivatives with a nitrile functionality (as opposed to alkyne cyclotrimerization to form benzene) proceeded smoothly (Scheme 31).…”
Section: Synthesis Of Substituted Benzene Derivativesmentioning
confidence: 99%
“…In this study, formation of a single regioisomer was observed. [52] The co-cyclotrimerization of two monoyne derivatives with a nitrile functionality (as opposed to alkyne cyclotrimerization to form benzene) proceeded smoothly (Scheme 31).…”
Section: Synthesis Of Substituted Benzene Derivativesmentioning
confidence: 99%
“…(242)) [1297]. Nickel catalyzed a related reaction of 1,6-, 1,7-and 1,8-diynes and nitriles to give fused bicyclic pyridines [1298]. Nickel catalyzed a cycloaddition of two alkynes and an isocyanate to give pyridones [1299].…”
Section: Cycloadditionsmentioning
confidence: 99%
“…Such a process has received considerable attention in recent years since it is synthetically useful, atom-economic, and environmentally benign [2]. Although a variety of stoichiometric methods have been described [3,4], catalytic systems are confined to iron [5], ruthenium [6], cobalt [7], rhodium [8], and nickel [9]. The detailed mechanism of these reactions is not yet fully established.…”
Section: Introductionmentioning
confidence: 99%